Spontaneous formation of three-dimensionally ordered Bi-rich nanostructures within GaAs1−xBix/GaAs quantum wells. (1st July 2016) - Luna, E; Wu, M; Hanke, M; Puustinen, J; Guina, M; Trampert, A
Abstract: In this work, we report on the spontaneous formation of ordered arrays of nanometer-sized Bi-rich structures due to lateral composition modulations in Ga(As, Bi)/GaAs quantum wells grown by molecular beam epitaxy. The overall microstructure and chemical distribution is investigated using transmission electron microscopy. The information is complemented by synchrotron x-ray grazing incidence diffraction, which provides insight into the in-plane arrangement. Due to the vertical inheritance of the lateral modulation, the Bi-rich nanostructures eventually shape into a three-dimensional assembly. Whereas the Bi-rich nanostructures are created via two-dimensional phase separation at the growing surface, our results suggest that the process is assisted by Bi segregation which is demonstrated to be strong and more complex than expected, implying both lateral and vertical (surface segregation) mass transport. As demonstrated here, the inherent thermodynamic miscibility gap of Ga(As, Bi) alloys can be exploited to create highly uniform Bi-rich units embedded in a quantum confinement structure.